Total thyroidectomy as primary surgical management for thyroid disease: surgical therapy experience from 5559 thyroidectomies in a less-developed region. Issue 1 (December 2015) - Hu, Jisheng; Zhao, Nan; Kong, Rui; Wang, Dawei; Sun, Bei; Wu, Lifeng
Abstract Background The objective of this study was to evaluate the safety of total thyroidectomy for thyroid disorders and summarise the treatment experience in a less-developed region. Methods This was a retrospective observational cohort study using the computerised database of the First Affiliated Hospital of Harbin Medical University. All consecutive thyroidectomy patients from 2003 to 2014 were included in this study. Demographics, surgical procedure, diagnoses, morbidity and mortality were retrospectively reviewed. Results There were a total of 714 men and 4845 women in this study, with a mean age of 55 (range 9–87) years. A total of 4632 patients underwent total thyroidectomy for primary surgical treatment, and 189 patients previously underwent partial thyroidectomy. A total of 56.2 % of the patients had multinodular goitre, including 12.23 % who were thyrotoxic. Graves' disease and Hashimoto's disease were diagnosed in 2.82 and 7.23 % of the patients, respectively. Papillary thyroid cancer was identified in 1336 patients, 44.99 % of whom had papillary microcarcinoma. The total prevalence of permanent complications of first-time and secondary surgeries was 0.35 and 7.41 %, respectively. During thyroid surgery, 945 patients underwent parathyroid autotransplantation. Conclusions Initial total thyroidectomy can be safely performed for both benign and malignant thyroid diseases in a less-developed region. The morbidity of a secondary surgical procedure after subtotal thyroidectomy is significantly high compared to first-time surgery.